2006
DOI: 10.1088/0953-8984/18/10/013
|View full text |Cite
|
Sign up to set email alerts
|

Search for half-metallic ferrimagnetism in V-based Heusler alloys Mn2VZ (Z = Al, Ga, In, Si, Ge, Sn)

Abstract: Abstract.Using a state-of-the-art full-potential electronic structure method within the local spin density approximation, we study the electronic and magnetic structure of Mn 2 V-based full Heusler alloys: Mn 2 VZ (Z=Al, Ga, In, Si, Ge, and Sn). We show that small expansion of the calculated theoretical equilibrium lattice constants restores the half-metallic ferrimagnetism in these compounds. Moreover a small degree of disorder between the V and Z atoms, although iduces some states within the gap, it preserve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 34 publications
(40 reference statements)
5
93
0
Order By: Relevance
“…In reference [48] we studied the possibility of appearance of half-metallicity in the case of the full-Heusler compounds Mn 2 VZ where Z is an sp atom belonging to the IIIB or IVB column of the periodic table. Total energy calculations have shown that, when Z is Al, Ga, In or Sn, the compounds are ferrimagnetic, while the compounds containing Si and Ge are non-magnetic at the equilibrium lattice constant.…”
Section: Half-metallic Ferrimagnetsmentioning
confidence: 99%
“…In reference [48] we studied the possibility of appearance of half-metallicity in the case of the full-Heusler compounds Mn 2 VZ where Z is an sp atom belonging to the IIIB or IVB column of the periodic table. Total energy calculations have shown that, when Z is Al, Ga, In or Sn, the compounds are ferrimagnetic, while the compounds containing Si and Ge are non-magnetic at the equilibrium lattice constant.…”
Section: Half-metallic Ferrimagnetsmentioning
confidence: 99%
“…The crystalline structure typical for half-Heusler materials is the non-centrosymmetric cubic structure C1 b ; Heusler (1903); Webster et al (1988), while full-Heusler alloys crystallize in the cubic space group with Cu 2 M nAl (L2 1 ) prototype Heusler (1903);Webster et al (1988) or Hg 2 CuT i prototype, if the number of 3d electrons of Y atom exceeds that of X 2 atom Kandpal et al (2007). In the last decades, M n 2 , Co 2 , F e 2 or Cr 2 -based Heusler alloys have been widely studied Buschow et al (1981); Chen et al (2006); Kumar et al (2010); Graf et al (2011);Weht et al (1999); Ozdogan et al (2006);Fecher et al (2006); Galanakis et al (2007);ZhongyuYao et al (2010); Luo et al (2007); Li et al (2009), however only few of T i 2 -based full Heusler alloys were investigated Kervan et al (2012); Pugaczowa-Michalska Maria (2012); Kervan et al (2011);Lei et al (2011). In the present paper, the half metallic properties of T i 2 CoSn are theoretically investigation by first-principles calculations of density of states, energy bands, and magnetic moments.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of such an ideal compound, half-metallic ferrimagnetism is highly desirable since such compounds would yield lower total spin moments than their ferromagnetic counterparts. Some perfect Heusler compounds like FeMnSb [23] and Mn 2 VAl [24] are predicted to present half-metallicity in conjunction with ferrimagnetism. Recently other routes to half-metallic ferrimagnetism have been studied like the doping of diluted magnetic semiconductors [25], and the inclusion of defects in Cr pnictides [26] and Co 2 CrAl(or Si) full-Heusler alloys [27].…”
Section: Introductionmentioning
confidence: 99%